Green IS – External Pressures and IS Executives - Hassmann, Tobias (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
Addressing the urgent need for sustainable solutions aligned with the United Nations' (UN) Sustainable Development Goals (SDGs) requires collective action across all societal levels, including the information systems (IS) discipline. One strand of IS research focuses on understanding how IS executives' actions and beliefs contribute to sustainability outcomes through Green IS practices. This research proposes to investigate how external pressures influence IS executives’ perceptions of the salience of sustainability issues, and how these perceptions, in turn, shape their Green IS-related actions and underlying beliefs. Adopting a qualitative research design, the proposed research study spans two phases: first, expert interviews with IS executives experienced in Green IS will be conducted to explore their perspectives. Second, a case study will validate and deepen these findings by identifying the factors that influence executives’ Green IS actions and beliefs, and examining how and why these factors exert their influence. The proposed research aims to generate both theoretical contributions to Green IS and practical insights for organizations seeking to enhance sustainability through IS leadership.